(untitled) (Research, Society and Development, 2020)
This article is the result of research linked to the Graduate Program in Professional and Technological Education, Master’s Program at the Federal Institute, at the Blumenau campus. Its theme is social and economic indicators, as an instrument in the process (re) knowledge of the context of performance of a campus of the Federal Institute. Based on the reflections made in this research in relation to the proximity and distances of a campus, with regard to its legal commitment, we seek to answer the extent to which social and economic indicators contribute to management in decision making. From the purposes of the Federal Institutes, according to Law 11,892 / 2008, it is understood that a campus is committed to contributing to its area of ​​coverage. This issue calls for, among other aspects, the constant (re) knowledge of Local Productive, Social Cultural Arrangements, with the mapping of socioeconomic and cultural potentialities of reality, an indispensable factor to be observed, whether in the course of implanting and implementing a campus Federal Institute, as well as in the process of continuous (re) evaluation of its offers. As for the approach, the research was characterized by qualitative and quantitative; applied in nature; regarding its objectives, exploratory and descriptive; bibliographic / documentary and field research in relation to its procedures. Regarding the results obtained, the gap in the definition of the area covered by a campus stands out, the construction of a database with indicators disaggregated by municipalities and their historical series.